Diagnostic Value of Addition First One Minute Abnormal Heart Rate Recovery After Exercise Treadmill Test in Moderate Risk Duke Treadmill Score to Detect Severe Coronary Artery Lesion in Patient Suspected Stable Coronary Artery Disease - N Nurkusumasari (Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada, 2017)
Background: Duke Treadmill Score (DTS) and first one minute abnormal heart rate recovery .......